Estudo sobre as relações entre a fenomenologia e a gestalt-terapia: contexto, aparições terminológicas e sentidos entrelaçados - Almeida, Josiane Maria Tiago de (2022)
The aim of this study was to investigate the contribution of Edmund Husserl's Phenomenology in the constitution of Gestalt-therapy, through the analysis of the gestalt work, published in 1951, "Gestalt-therapy" (Gestalt Therapy: Excitement and Growth in The Human Personality), written by Frederick Perls (1893-1970), Ralph Hefferline (1910-1974) and Paul Goodman (1911-1972). In the first chapter, we historically describe the approximation between the Gestalt approach and Husserlian philosophy analyzing three periods: 1) Fritz Perls and influences on European soil; 2) foundation of Gestalt-therapy on American soil; 3) Gestalt-therapy and connections with Humanistic Psychology. The method used was qualitative research as formulated by Lima and Mioto (2007). We verified three most relevant theories in the Gestalt epistemological constitution in the European period: Psychoanalysis, Organismic Theory and Gestaltheorie. About the phenomenology, Laura Perls and Paul Goodman report contact with some authors and with Husserl's work 'Ideas', without specifying the depth of their studies. Regarding the gestalt connections with humanist approaches and possible phenomenological influence, we verified that there was a parallelism of interests, without deepening in relation to Phenomenology. We conclude that there was no significant conceptual approximation of Gestalt-therapy theorists in relation to phenomenological philosophy until the publication of the work 'Gestalt-therapy' that justified affirming it as a basic theoretical influence. In the second chapter, we investigate the influence of phenomenological philosophy in the elaboration of the work “Gestalt-therapy”, from the meanings mentioned and explained literally by the authors. The method was the historiography of Joseph Brožek (1998), organized from the bibliographic research of Lima and Mioto (2007). We analyzed the citations of the terms “phenomenology” and derivatives, and names of authors linked to phenomenological philosophy. We highlight the main meanings: 1) Postulate of consciousness (awareness) as a process where phenomenology would serve to describe its manifestation and functioning. 2) Emphasis on the experiencing subject as the creator of his own reality and on phenomenology as a tool in the description of conscious experience. 3) Proposition of Gestalt-therapy as an alternative scientific theory to the positivist and causal science model, using phenomenology as a foundation. Finally, in the last chapter, we discuss the correspondence between the 'gestalt' meanings of Phenomenology found in the previous chapter and its original meanings, carrying out a conceptual-interpretative reading (Lima and Mioto, 2007). Regarding the first sense, although it moves away from the notion of psychoanalytic consciousness, there is no approximation of the concept of awareness with that of phenomenological consciousness in Husserl. Regarding Phenomenology as a descriptive resource, we identified significant differences between “phenomenological description” and “gestalt description”. Finally, in relation to the science model, we observe distinctions in relation to the direction that each one of those theories needs to base its theoretical set. Finally, we identified a possible influence of Pragmatism and Functionalism on the Gestalt concepts of “consciousness” and “experience”, more significant than the conventional one attributed to Phenomenology. Finally, making an equivalence between the gestalt senses of Phenomenology and its original senses, we conclude that there is no clear and evident evidence that indicates that Husserlian Phenomenology has been epistemologically and methodologically used in the writing of the work “Gestalt-therapy”.